Peningkatan Motivasi Belajar untuk Mengembangkan Kreativitas di Panti Asuhan Yatim Piatu Al Ikhwaniyah, Jurang Mangu Barat, Tangerang Selatan - Sekar Arum Widha Ningsih; Annisa Annisa; Halda Oktaviani; Irfan Rizka Akbar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Abstract. This study aims to analyze the role of increasing learning motivation in developing children's creativity at the Al Ikhwaniya Orphanage, West Mangu Gorge, South Tangerang. The background of the research departs from the need to strengthen the quality of learning in the orphanage environment, where limited facilities, mentoring, and learning stimuli often have an impact on low motivation and the development of children's creativity. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results show that strategies to increase learning motivation, such as the application of activity-based learning methods, providing positive feedback, and creating a supportive learning environment, significantly contribute to improving creative thinking skills, problem-solving skills, and children's courage in coming up with new ideas. These findings confirm that learning motivation is a key factor in encouraging the development of children's creativity in orphanages. Thus, a sustainable and structured mentoring program is needed to maintain and optimize the development of children's creativity in the long term. Keywords: learning motivation, creativity, orphanage, self-development, activity-based learning, educational mentoring.